2004
DOI: 10.1007/s11159-004-4629-4
|View full text |Cite
|
Sign up to set email alerts
|

Globalisation And Local Indigenous Education In Mexico

Abstract: Globalisation is often viewed as a threat to cultural and linguistic diversity and therefore is a central concern of educational practices and policy. The present study challenges this common view by demonstrating that local communities can use global means to support and enhance their specific practices and policies. An historical exploration of education policy in Mexico reveals that there has been a continuing struggle by indigenous peoples to maintain locally relevant modes of teaching. Indigenous peoples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This is consistent with the findings of De Janvry and Sadoulet (2001), who found that indigenous individuals from rural Mexico are less likely to work in the nonagricultural sector given any level of education. Indigenous minorities in Mexico often have been excluded from public benefits, including education (Despagne, 2013; Reinke, 2004; United Nations: Economic Commission for Latin America and the Caribbean ( ECLAC), 2014). However, unlike De Janvry and Sadoulet (2001), we do not find significantly different effects of school construction on women's education or labor outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the findings of De Janvry and Sadoulet (2001), who found that indigenous individuals from rural Mexico are less likely to work in the nonagricultural sector given any level of education. Indigenous minorities in Mexico often have been excluded from public benefits, including education (Despagne, 2013; Reinke, 2004; United Nations: Economic Commission for Latin America and the Caribbean ( ECLAC), 2014). However, unlike De Janvry and Sadoulet (2001), we do not find significantly different effects of school construction on women's education or labor outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing that indigenous people are just as vulnerable as others in society to pressures to make a living, to grow food, and to have new media and transportation options, they see the costs and environmental impact of local trade-offs. Extending this trend into cyberspace, indigenous groups fight for cultural survival, formal recognition, and free exercise of their internationally, if not locally, recognized human rights (Reinke 2004). These new forms of alliance, outreach, and literacy are transforming what it means to be indigenous in Latin America and the Caribbean.…”
Section: Regional Perspective From Latin Americamentioning
confidence: 99%
“…In reality, however, the implementation of bilingual and intercultural education in indigenous communities has been uneven at best. Acculturation has prevailed over language maintenance, for Spanish continues to be the primary language of instruction in many bilingual education programs; at the same time, federal control over the national curriculum has remained steady, limiting local participation and control over curriculum content (Hamel, 2008b; King, 1994; Reinke, 2004).…”
Section: Shifting Representations Of Youth and Literacy In Latin Amermentioning
confidence: 99%